2022
DOI: 10.3389/fcvm.2021.798364
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro-Cardiovascular Risk, Target Organ Damage, and Treatment Outcomes in Primary Aldosteronism

Abstract: Primary aldosteronism (PA) is the most common type of endocrine hypertension, and numerous experimental and clinical evidence have verified that prolonged exposure to excess aldosterone is responsible for an increased risk of cerebro-cardiovascular events and target organ damage (TOD) in patients with PA. Therefore, focusing on restoring the toxic effects of excess aldosterone on the target organs is very important to reduce cerebro-cardiovascular events. Current evidence convincingly demonstrates that both su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 229 publications
(289 reference statements)
0
11
0
Order By: Relevance
“…An enhanced risk of atherosclerotic cardiovascular and cerebrovascular diseases in PA patients has been reported ( 7 , 8 , 49 ). A theory has been proposed that in PA, excess aldosterone can lead to arterial wall thickening and fibrosis, and that increased oxidative stress and inflammation can result in endothelial dysfunction ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced risk of atherosclerotic cardiovascular and cerebrovascular diseases in PA patients has been reported ( 7 , 8 , 49 ). A theory has been proposed that in PA, excess aldosterone can lead to arterial wall thickening and fibrosis, and that increased oxidative stress and inflammation can result in endothelial dysfunction ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the effect of sodium retention and electrolyte dysregulations, studies have demonstrated that PA is also related to endothelial dysfunction, fibrosis, increased oxidative stress and increased risk of cardiac fibrosis ( 5 , 6 ). These adverse mechanisms may explain the significantly increased risk of cardiovascular and cerebrovascular diseases in PA compared to essential hypertension (EH) patients ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to elevated aldosterone levels might result in substantial cardiovascular damage independent of blood pressure [2]. It has been associated with cardiovascular damage and with marked target organ damage affecting the heart, the carotid artery, or the kidney [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that the causal relationship between PA and the risk of CVDs remains controversial. In addition, studies have shown that acute myocardial infarction was associated with high aldosterone secretion exacerbating myocardial damage [15,16] and further leading to the occurrence of adverse events (OR = 1.1, 95%CI: 1.03-1.15) [17], and PA showed prevalent among hypertensive patients with unexplained atrial brillation, up to 42% (95%CI: 31.8-53.9)[18], highlighting the bidirectional association between PA and CVDs.…”
Section: Introductionmentioning
confidence: 99%